Tensile properties of vulcanized field natural rubber latex by electron beam - Chai , Chee Keong; Wan Manshol W. Zin; Md. Soot Hj. Ahmad (Universiti Kebangsaan Malaysia, 2008)
Electron beam vulcanization of natural rubber latex has been developed as an alternative to the conventional sulphur vulcanization method. This study aimed at determining the effect of electron beam dose, beam current and centrifugation to the tensile properties of field natural rubber latex. Irradiation dose and beam current ranged from 50 to 300 kGy and 1 to 15 mA respectively. The determination of tensile properties were done on cast film prepared from irradiated field latex before and after centrifugation. It was found that tensile properties increased with radiation dose but decreased with beam current. Rubber films made from centrifuged irradiated field latex were softer and showed higher tensile strength.